Deixis in Political Discourse: A Pragmatic Analysis of “What’s behind Widespread Unrest in Indonesia?” - Sitorus, Tessalonika Kristina; Gea, Juni Ana; Sari, Angel Aulia; Saragih, Erikson (Journal of English Language and Education, 2025)
The research focuses on analyzing the deixis used in the Al Jazeera English Inside Story episode “What’s Behind the Widespread Unrest in Indonesia?” and aims to examine what types of deixis are used and how these deictic expressions function pragmatically to depict Indonesia’s socio-political crisis in international media discourse. A qualitative descriptive approach is used to analyze 341 deictic expressions in the episode’s script using Levinson’s (1983) five types of deixis, i.e. personal, spatial, temporal, social and discourse. The findings show that personal deixis is the most prominent one, in which the perspective particularization and responsibility attribution by the interlocutors lead to mutual alignment (all participants’ identity alignments) and, however, time and discourse deixis strengthen the construction of collective immediacy and coherence of the narratives. Although the spatial and social deictics are the least frequent, they still employ the spatial grounding of the events and the indication of power relations hierarchy. The findings indicate that in the international media discourse, deixis functions not only as a referential strategy, but also as a pragmatic device in the context of political events framing and the manipulation of the audiences’ interpretations. These results extend previous deixis research by highlighting its role in global news reporting and offering insights into how linguistic choices contribute to the international framing of Indonesia’s political unrest.